(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the socio-pedagogical foundations of developing the knowledge of future physical education teachers about sports tourism, the fact that today tourism has become an important social sphere for every country, the individual-psychological characteristics of the sphere of sports tourism, and the sphere of their motives are thoroughly studied and comments are highlighted.